Pendekatan Brief DBT untuk Menurunkan Gejala Kecemasan dan Kesulitan Regulasi Emosi pada Remaja Perempuan - Utami, Melati Nur; Djuwita, Efriyani (Universitas Muhammadiyah Metro, 2023)
Changes in physical, cognitive, emotional, and social interactions in female adolescents are associated with the onset of anxiety disorder. Furthermore, during middle adolescence, adolescents tend to use maladaptive emotion regulation strategies. Difficulties in emotion regulation are associated with the emergence and the increased intensities of anxiety. Dialectical Behavioral Therapy is an evidence-based intervention to increase emotion regulation skill and to decrease anxiety symptoms. This study is a training with a brief Dialectical Behavioral Therapy approach aimed to reduce anxiety symptoms in 6 female adolescents (grade 10). Results showed that the training significantly reduced the level of anxiety symptoms. Meanwhile, although there were declines in the pre and post-test scores of emotion dysregulation, the scores differences were not significant. Training duration and invalidating environment were identified as factors contributing to the insignificant reduction of the emotion dysregulation level.